Strategi Pemasaran Public Relations Dalam Meningkatkan Pengguna Kartu Brizzi (Studi Kasus Pada PT. Bank Rakyat Indonesia (Persero), Tbk Kantor Cabang Balikpapan Sudirman) - Oktri Nur Annissa; Dessy Handa Sari; Ramli . (Eco-Entrepreneur, 2022)
This study aims to determine the marketing strategy of PT. Bank Rakyat Indonesia (Persero), Tbk Branch Office Balikpapan Sudirman in increasing BRIZZI card users. This type of research used qualitative research with qualitative descriptive methods. Data collection techniques using interviews and documentation. The results of the research can be seen that the Public Relations marketing program in increasing the number of BRIZZI card users by conducting special event programs, sponsorships, and BRIZZI co-branding or collaborating with PT. Bank Rakyat Indonesia (Persero), Tbk Branch Office Balikpapan Sudirman is said to be effective. It can be seen from the increase in the number of BRIZZI card users every month during 2021 which continues to increase despite the implementation of Community Activity Restrictions (PPKM). This study also found obstacles in introducing BRIZZI cards to the people of Balikpapan City, namely the lack of public understanding of the uses and functions of BRIZZI.